2014
DOI: 10.1038/bmt.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis obliterans in patients undergoing allogeneic hematopoietic SCT

Abstract: Bronchiolitis obliterans (BO) is a severe pulmonary complication of allo-SCT. This study evaluated the incidence of BO in patients undergoing allo-SCT in Hospital Universitário da Universidade Federal do Paraná, risk factors for developing this complication and prognostic factors for those patients who developed this entity. The study included 1286 patients transplanted between 1979 and 2009 who survived for 100 days or more. We diagnosed 53 cases of BO. The cumulative incidence was 2.9% in 1 year and 3.7% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 17 publications
(33 reference statements)
2
13
1
Order By: Relevance
“…Previous studies reported that a short duration from transplantation to the development of BOS was a poor prognostic factor of BOS after HSCT. [19,20] We did not find an association between the time from transplantation to the BOS diagnosis and survival, FEV 1 decline, or progression of CT findings. Adjustment by multivariate analysis showed that the duration was not a confounder for the relationship between CAI and survival.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies reported that a short duration from transplantation to the development of BOS was a poor prognostic factor of BOS after HSCT. [19,20] We did not find an association between the time from transplantation to the BOS diagnosis and survival, FEV 1 decline, or progression of CT findings. Adjustment by multivariate analysis showed that the duration was not a confounder for the relationship between CAI and survival.…”
Section: Discussioncontrasting
confidence: 53%
“…BOS is an NIPC of particular interest because it is associated with increased mortality after transplantation, a high burden of respiratory symptoms, poorer outcomes, and a lower quality of life. 20,21 Our findings in BOS patients mirror those in the matched patients with NIPCs, showing higher health-related costs in all years, although these costs may reflect patients with more severe and rapidly advancing disease and those with disease that develops more slowly. 22 In either case, however, increased immunosuppression, which is associated with a higher risk of infection, may be especially harmful to patients with significant lung disease due to BOS.…”
Section: Discussionsupporting
confidence: 72%
“…We did not identify BOS within 9 months of A-HCT. Because BOS typically manifests 12-18 months after transplantation, screening may be more efficient if started later in the course of transplantation (10,24). Alternatively, targeting A-HCT recipients at high risk for BOS, such as those with recent viral lower respiratory infection (25) or active chronic GVHD (26), may be fruitful.…”
Section: Discussionmentioning
confidence: 99%